A New Type of Reduced Dimension Path Following Methods (Journal of Computational Mathematics, 1992)
To solve $F(x)=0$ numerically, we first prove that there exists a tube-like neighborhood around the curve in $R^n$ defined by the Newton homotopy in which $F(x)$ possesses some good properties. Then in this neighborhood, we set up an algorithm which is numerically stable and convergent. Since we can ensure that the iterative points are not far from the homotopy curve while computing, we need not apply the predictor-corrector which is often used in path following methods.